PERAN PERSONAL DAN RELASIONAL GURU TERHADAP TRUST SISWA DI PONDOK PESANTREN RAHMATUL ASRI - Nur Akmal; Widyastuti Widyastuti (Jurnal Psikologi TALENTA, 2021)
This research aims to determine the effect of personal and relational attributes on student trust to teachers. The participants in this study are students and students at Pondok Pesantren Rahmatul Asri Maroangin Enrekang. 317 people (Male = 154, Female = 163) with an age range of 11 to 18 years. This research instrument uses a scale of trustworthiness developed by Faturochman and Minza. Reliability of research instruments amounted to 0.953 omega coefficients, with the discrimination power of the item ranging from 0.344 to 0.740.  The data analysis techniques in this study use multiple regression analysis. The results showed that personal and relational attributes were together correlated with 0.798 student trusts with a contribution of 63.3%.